Successful Treatment of Mucocutaneous Lupus Erythematosus in a Dog with Prednisolone, Mycophenolate Mofetil and Tacrolimus - Jae-Eun Hyun; Yeong-Hun Kang; Cheol-Yong Hwang (Veterinary Sciences, 2021)
A 6-year-old, intact male miniature Pinscher dog had erosive lesions on perilabial, peripenial and perianal mucocutaneous areas, which were exacerbated by ulcerations, crusts, with pain while defecating and urinating. The lesions were symmetrical, and no systemic signs were observed. Histopathological evaluation showed parakeratotic hyperkeratosis, ulceration and cell-rich lymphoplasmacytic interface dermatitis with basal keratinocyte apoptosis. Immunohistochemistry revealed strong reaction in the dermoepidermal junction against goat-canine IgG and mild-to-moderate reaction against goat-canine IgA, IgM and C3. Based on these findings, the dog was diagnosed with mucocutaneous lupus erythematosus (MCLE). Oral prednisolone 1 mg/kg twice daily, mycophenolate mofetil (MMF) 18.3 mg/kg twice daily and 0.1% tacrolimus ointment were prescribed as initial treatment. The lesions showed remarkable improvement within 4 weeks, but the dog exhibited polyuria, polydipsia and hepatomegaly with high dosage of prednisolone. Hence, the dosage of prednisolone was gradually tapered for 9 weeks and discontinued, but MMF and tacrolimus were continued. No new lesion or associated side effect was observed while reducing the MMF dose to 10 mg/kg twice daily and with continuous use of tacrolimus ointment after steroid discontinuation. In conclusion, this case report emphasizes the usefulness of MMF and tacrolimus as steroid-sparing agents in the treatment of dogs with MCLE. To the best of our knowledge, this is the first case report of MCLE that was successfully managed long-term with MMF and tacrolimus.